Applications of Operation research in the Field of IOT - et. al., Navleen Kaur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
These days Internet of Things (IoT) increased an extraordinary consideration structure specialist, since it turns into a significant innovation that guarantees a shrewd individual life, by permitting an interchanges between objects, machines and each thing together with people groups. IoT speaks to a framework which comprises a things in reality, and sensors joined to or consolidated to thesethings, associated with the Internet through wired and remote system structure.In this paper I have represented the various application of the operation research in the field of IoT.